Tall walls and high fences: officers and offenders, the Texas prison story - Alexander, Bob (North Texas crime and criminal justice series, 2020)
"Punishment of the refractory" -- "Muzzle the guard" -- "Afraid they will kill Me" -- "Until his body be dead" -- "Just like anybody's grandmother" -- "Only themselves to blame" -- "put them on the spot" -- "so he can better handle a shotgun" -- "Before he whacks you" -- "Guts, Heart--and six rounds" -- "Not dealing with Sunday school kids" -- "An Unwilling Pioneer" -- "Violent Convicts Commit violent acts" -- "nothin' left to lose" -- "die an outlaw's death" -- Appendix A. Fallen Heroes and Heroines -- Appendix B. Talking the Talk: A Prison Glossary.